2017
DOI: 10.1101/161182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speed breeding: a powerful tool to accelerate crop research and breeding

Abstract: The growing human population and a changing environment have raised significant concern for global food security, with the current improvement rate of several important crops inadequate to meet future demand [1]. This slow improvement rate is attributed partly to the long generation times of crop plants. Here we present a method called 'speed breeding', . CC-BY 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…The generation time of most plant species represents a 33 bottleneck in applied research programs and breeding, creating the need for technologies that 34 accelerate plant development and generation turnover. Recently we reported protocols for 'speed in barley, and pod shattering in canola 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The generation time of most plant species represents a 33 bottleneck in applied research programs and breeding, creating the need for technologies that 34 accelerate plant development and generation turnover. Recently we reported protocols for 'speed in barley, and pod shattering in canola 1 .…”
mentioning
confidence: 99%
“…22 °C / 17 °C for 22 hours light and 2 hours dark, respectively, is used at JIC (Speed breeding I) 1 . In…”
mentioning
confidence: 99%
“…Recently, the "speed breeding" technique has been implemented in wheat, which uses extended day lengths of 22 hours and improved light quality to accelerate the generation time in wheat (Watson et al, 2018). Reduction of generation times to 8-10 weeks is achieved through an accelerated growth rate and harvesting of immature seeds 2-3 weeks post anthesis.…”
Section: Speed Breeding To Accelerate Crossing and Phenotypingmentioning
confidence: 99%
“…Incorporating speed breeding within crossing programmes can reduce the time required to produce and phenotype double mutants in tetraploid wheat to less than 7.5 months and triple mutants in hexaploid wheat to less than 10 months (Figure 4). In addition to reducing generation times, it has been shown that several traits of interest such as disease resistance, height and flowering time can be properly characterised under speed breeding conditions (Watson et al, 2018).…”
Section: Speed Breeding To Accelerate Crossing and Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation